Paediatric cardiac catheterisation in Norway: rates and types of complications in new terms. (8th March 2017) - Ravndal, Maren E. A.; Christensen, Anders H.; Døhlen, Gaute; Holmstrøm, Henrik
Abstract: We determined the incidence, type, and severity of complications after cardiac catheterisation in children with heart disease in Norway, and we present the results in terms of the International Paediatric and Congenital Cardiac Code (IPCCC) nomenclature for complications. All paediatric cardiac catheterisations in Norway are performed in one clinical centre. All procedures performed during a 5-year period beginning in 2010 were prospectively registered, and medical records for cases with complications were reviewed to confirm the event and to re-classify the type, severity, and attributability of the complication according to the IPCCC nomenclature. Univariate and multivariate analyses were performed to identify possible risk predictors. A total of 1318 catheterisations performed on 941 patients were included in the present study, of which 68% were interventional. The complication and major complication rates were 5.5 and 1.4%, respectively. Trauma to the vessels or the myocardium, haemodynamic adverse events, and arrhythmias were the most common types of complications. In the multivariate model, weight <4 kg (odds ratios, 3.0; 95% confidence intervals: 1.6–5.8) and risk category 5 (odds ratios, 5.1; 95% confidence intervals: 2.1–12.3) were significant risk predictors for any complication. In spite of a high rate of interventions, the complication rates in this study were similar to older studies, but diverging methods and terminology limit the comparability. We strongly suggest general use of the proposed IPCCC classification system for registration and reports of complications for paediatric cardiac catheterisations.